Texture-modified food and fluids in dementia and residential aged care facilities - Painter V (Dove Medical Press, 2017)
Virginia Painter,1 David G Le Couteur,1–3 Louise M Waite1–3 1Aged and Chronic Care Department, Concord Repatriation General Hospital, Concord, NSW, Australia; 2Ageing and Alzheimer’s Institute, Concord Repatriation General Hospital, Concord, NSW, Australia; 3Centre for Education and Research on Ageing, University of Sydney, Concord, NSW, Australia Introduction: Dysphagia is common in people living with dementia and associated with increased risk of aspiration pneumonia, dehydration, malnutrition, and death. Treatment options are limited and the use of texture-modified food and fluids (TMF) is a widespread clinical practice. This review aimed to evaluate the evidence for TMF in dementia.Methods: A literature search using terms “dysphagia,” “texture-modified food and fluids,” “dementia,” and “aged care” was performed by using three electronic databases from 1990 to March 2017. Studies were assessed for suitability, then reviewed with data extracted, and grouped by categories of outcome measures.Results: A total of 3,722 publications were identified, and 22 studies met the inclusion criteria. Studies were heterogeneous in design and methodology. There were no publications examining dementia exclusively; however, many subjects with dementia were included in studies of residential aged care facilities. TMF reduced the risk of aspiration seen on videofluoroscopy but not clinical aspiration and pneumonia. TMF was associated with lower daily energy and fluid intake and variable adherence.Conclusion: There is a lack of evidence for people living with dementia and in residential care facilities that TMF improves clinical outcomes such as aspiration pneumonia, nutrition, hydration, morbidity, and mortality. Adverse effects including poorer energy and fluid intake were identified. Keywords: modified diet, dysphagia, aspiration, aged care, nursing homes, dehydration, nutrition